The Characteristics of Mathematics Daily Test Items - Saputro, Totok Victor Didik; Silvester, Silvester; Purnasari, Pebria Dheni (Journal of Learning Improvement and Lesson Study, 2023)
The items which are qualified and have good category are obtained through the characteristics of test item analysis. The research aimed to know the characteristics of mathematics daily test items of tenth-grade senior high school. The research used explorative descriptive with a quantitative approach. The data were obtained from the results of 20 test item documentation of 124 tenth-grade students of SMA Marsudirini Bekasi. The daily test was validated by experts and analyzed used classical test theory. The results of this research showed the content validation index was more than 0,8 that test items categorized very valid. The difficulty level index of test items included three categories as big as 20% of test items in easy category, 70% of test items were in the medium category, and 10% of test items were in the hard category. The quality of test items obtained as big as 30% of test items in the adequate category and 70% of test items in the good category.